2004
DOI: 10.1590/s0103-64402004000100008
|View full text |Cite
|
Sign up to set email alerts
|

Control of gingival inflammation in a teenager population using ultrasonic prophylaxis

Abstract: Gingival inflammation is clinically characterized by gingival redness, swelling and increased tendency of bleeding of the soft tissue. Bacterial biofilm is the etiological agent. If, at this stage, the bacterial biofilm is removed and appropriate control methods are applied, remission of gingival inflammation occurs. This study evaluated the effectiveness of a single session of ultrasonic prophylaxis for the reduction of gingivitis in an adolescent population using the Plaque Index (PI) and Gingival Index (GI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…Investigating an antimicrobial that could be used on a daily basis seemed to be very helpful for patients with diabetes, considering their susceptibility to gingival inflammation. Although Novaes Júnior 37 reported that a single session of ultrasonic prophylaxis combined with oral hygiene instructions was sufficient to treat gingivitis in adolescents (as assessed 15 and 30 days after treatment), this result is not observed in the present study. At 3 months, no clinical improvements were detected in the patients with or without diabetes who only received ultrasonic debridement (placebo groups), although it cannot be confirmed that improvements did not occur in the first month.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Investigating an antimicrobial that could be used on a daily basis seemed to be very helpful for patients with diabetes, considering their susceptibility to gingival inflammation. Although Novaes Júnior 37 reported that a single session of ultrasonic prophylaxis combined with oral hygiene instructions was sufficient to treat gingivitis in adolescents (as assessed 15 and 30 days after treatment), this result is not observed in the present study. At 3 months, no clinical improvements were detected in the patients with or without diabetes who only received ultrasonic debridement (placebo groups), although it cannot be confirmed that improvements did not occur in the first month.…”
Section: Discussioncontrasting
confidence: 79%
“…In systemically healthy patients with mild to moderate gingivitis, a fixed combination of four EOs demonstrated clear antiplaque and antigingivitis effects 22‐24,35,36 . Because ultrasonic debridement is believed to be an appropriate alternative to manual instrumentation, 37,38 the therapeutic approach selected for the present study involved the daily use of EO after ultrasonic debridement in a group of patients with diabetes. To the best of the authors’ knowledge, having a placebo as the comparator, the design of the present study also answered for the first time whether the adjunctive use of EO provides additional benefits based on different gingivitis indicators, even in the presence of diabetes.…”
Section: Discussionmentioning
confidence: 99%